TEACHERS’ PERCEPTIONS ON THE CONCEPT OF CLINICAL PRACTICE IN TEACHER EDUCATION - Kazu, İbrahim Yaşar; Kurtoğlu, Cemre (My University, 2019)
The 21st century has become a watershed in realizing the importance of high-quality clinicalprograms in teacher preparation. The main purpose of this research was to determine teachers'mental images about the concept of clinical practice in teacher education via metaphors. Thisresearch was carried out with 71 teachers working at secondary schools, in the 2017-2018academic year. The data were collected through an open-ended questionnaire named “A Form ofDetermination of Teachers’ Metaphors”. A phenomenology method which is a qualitative researchmethod was used. Teachers explained the concept of clinical practice in terms of the importanceof teacher education, the importance of collaboration among clinical teachers, clinical mentors andpreservice teachers, feedbacks from clinical teachers to preservice teachers and the length of thetraining program via metaphors. The data were analyzed by content analysis. Related data weregathered; and the name of the category, the context of the category, and the frequency of usagewere calculated for metaphors that reflect certain characteristic in each category. From themetaphors about clinical practice and the research field, it was inferred that participants perceivedthe field within a wide conjecture and interestingly projected its contributions to teachereducation. It was seen that the majority of teacher support practical education in teacher training.They expressed their opinions about this issue through different metaphors.
Keywords: Eğitim; Eğitim Araştırmaları